If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -3m = 7 + -6(m + 2) Reorder the terms: 16 + -3m = 7 + -6(2 + m) 16 + -3m = 7 + (2 * -6 + m * -6) 16 + -3m = 7 + (-12 + -6m) Combine like terms: 7 + -12 = -5 16 + -3m = -5 + -6m Solving 16 + -3m = -5 + -6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6m' to each side of the equation. 16 + -3m + 6m = -5 + -6m + 6m Combine like terms: -3m + 6m = 3m 16 + 3m = -5 + -6m + 6m Combine like terms: -6m + 6m = 0 16 + 3m = -5 + 0 16 + 3m = -5 Add '-16' to each side of the equation. 16 + -16 + 3m = -5 + -16 Combine like terms: 16 + -16 = 0 0 + 3m = -5 + -16 3m = -5 + -16 Combine like terms: -5 + -16 = -21 3m = -21 Divide each side by '3'. m = -7 Simplifying m = -7
| 10x-25=105 | | 80+x=171 | | 34+4x=-5(x+4) | | -3x-3(1+1)=-15 | | 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 | | 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 | | 2(a+3)=5a-1 | | -4-4(2+4v)=-44 | | a-4(2a+4)=-44 | | 10a=45 | | 3(2+4x)=-42 | | 5(y^2-14y+49)=-90 | | 5x-12a=7-2x | | 2.4(m-3)+3.8=-32 | | 3x(x)+8x=9 | | 10n^2-9n=9 | | 6(y+x+2+x+4)=18 | | 3(x+1)+2(x+2)=2x+10 | | 5=(-6x-9) |